Rate of Convergence of General Phase Field Equations in Strongly Heterogeneous Media Toward Their Homogenized Limit - Schmuck,M; Kalliadasis,S (SIAM Journal on Applied Mathematics, 2017)
Over the last few decades, phase field equations have found increasing applicability in a wide range of mathematical-scientific fields (e.g., geometric PDEs and mean curvature flow, materials science for the study of phase transitions) but also engineering ones (e.g., as a computational tool in chemical engineering for interfacial flow studies). Here, we focus on phase field equations in strongly heterogeneous materials with perforations such as porous media. To the best of our knowledge, we provide the first derivation of error estimates for fourth order, homogenized, and nonlinear evolution equations. Our fourth order problem induces a slightly lower convergence rate, i.e., $ε^{1/4}$, where $ε$ denotes the material's specific heterogeneity, than established for second order elliptic problems (e.g., [V. Zhikov, Dokl. Math., 73 (2006), pp. 96--99, https://doi.org/10.1134/S1064562406010261.]) for the error between the effective macroscopic solution of the (new) upscaled formulation and the solution of the microscopic phase field problem. We hope that our study will motivate new modeling, analytic, and computational perspectives for interfacial transport and phase transformations in strongly heterogeneous environments.